The role of epigenetic modifications in hematological cancers - Ilic, Jovana; Bold, Anna; Knop, Stefan (Frontiers in Oncology, 2026)
Epigenetic regulation of gene expression entails DNA methylation and histone modifications, which orchestrate chromatin structure and transcriptional activity. Aberrant regulation of these mechanisms contributes to the development and progression of hematological cancers. Mutations in enzymes mediating DNA methylation and histone modification patterns reshape chromatin structure, influencing transcriptional profiles, thus promoting oncogenesis, clonal evolution and drug resistance. This review focuses on significant alterations in DNA methylation patterns, mutations and changes in expression of histone modifying enzymes and chromatin remodeling complexes described in leukemias, lymphomas and multiple myeloma. We summarize the most prominent changes in epigenetic mediators and their impact on transcriptional activity and oncogenesis.